Significant underestimation of radiative forcing by aerosol–cloud interactions derived from satellite-based methods - Hailing Jia (Nature Portfolio, 2021)
Satellite-based estimates of radiative forcing by aerosol–cloud interactions are consistently smaller than those from global models, hampering accurate projections of future climate change. Here, the authors show that the discrepancy can be substantially reduced by correcting sampling biases induced by inherent limitations of satellite measurements.